Crystallographic study of self‐organization in the solid state including quasi‐aromatic pseudo‐ring stacking interactions in 1‐benzoyl‐3‐(3, 4‐dimethoxyphenyl)thiourea and 1‐benzoyl‐3‐(2‐hydroxypropyl)thiourea. Issue 1 (14th December 2016) - Okuniewski, Andrzej; Rosiak, Damian; Chojnacki, Jarosław; Becker, Barbara
Abstract : The reactions of benzoyl isothiocyanate with 3, 4‐dimethoxyaniline and 1‐aminopropan‐2‐ol yielded two novel 1‐benzoylthiourea derivatives. In both structures, intramolecular O—H…N hydrogen bonding is present, forming six‐membered pseudo‐rings that are quasi‐aromatic and interact with phenyl rings and with each other via stacking‐type interactions. Intermolecular hydrogen bonds result in the formation of centrosymmetric dimers or one‐dimensional chains. C—H…(O, S) interactions additionally reinforce the three‐dimensional structure of both compounds. Abstract : 1‐Benzoylthioureas contain both carbonyl and thiocarbonyl functional groups and are of interest for their biological activity, metal coordination ability and involvement in hydrogen‐bond formation. Two novel 1‐benzoylthiourea derivatives, namely 1‐benzoyl‐3‐(3, 4‐dimethoxyphenyl)thiourea, C16 H16 N2 O3 S, (I), and 1‐benzoyl‐3‐(2‐hydroxypropyl)thiourea, C11 H14 N2 O2 S, (II), have been synthesized and characterized. Compound (I) crystallizes in the space group P, while (II) crystallizes in the space group P 21 / c . In both structures, intramolecular N—H…O hydrogen bonding is present. The resulting six‐membered pseudo‐rings are quasi‐aromatic and, in each case, interact with phenyl rings via stacking‐type interactions. C—H…O, C—H…S and C—H…π interactions are also present. In (I), there is one molecule in the asymmetric unit. Pairs of molecules are connected via two intermolecular N—H…S hydrogen bonds, forming centrosymmetric dimers. In (II), there are two symmetry‐independent molecules that differ mainly in the relative orientations of the phenyl rings with respect to the thiourea cores. Additional strong hydrogen‐bond donor and acceptor –OH groups participate in the formation of intermolecular N—H…O and O—H…S hydrogen bonds that join molecules into chains extending in the [001] direction.